Quality assessment and quality control of next-generation sequencing for Leishmania infantum - Guerra, Juliana Mariotti; Fernandes, Natália Coelho Couto de Azevedo; Barbosa, José Eduardo de Raeffray; Taniguchi, Helena Hilomi; Hiramoto, Roberto Mitsuyoshi; Tolezano, José Eduardo; Cogliati, Bruno (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2016)
Next-generation sequencing (NGS) technologies are becoming widely used, and although a massive number of sequences can be generated in a single experiment, it is still important to characterize the reads. Characterizing reads may prevent undesirable outcomes in the assembly or mapping processes. Discarding low-quality reads, controlling for contamination, and trimming adaptor sequences are examples of preliminary quality control procedures that can be applied to raw reads before further analysis. Here it was applied the FastQ Quality Control Software (FastQC) in order to assess the quality of the data of next-generation sequecing for Leishmania infatum.